2022
DOI: 10.5539/res.v14n2p64
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Distance Education, During the Covid-19 Pandemic: Greek Teachers’ Opinions

Abstract: In Greece, the COVID-19 pandemic resulted in the schools' closure during the 2019-2020 school year. The Ministry of Education tried to develop online platforms so that the students could have access to education. The use of distance learning came to the fore. The teachers used the online teaching tools available as a response to this challenging situation. Nevertheless, most of them had not received any relevant training and had at their disposal minimal resources, mainly of their own and not public on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Educators concluded that the distance education offered a medium of communicating with their students (Anastasiades, 2020• Manesis et al, 2022. However, it cannot replace the team's dynamics within a school classroom, since it is a lonely method of learning (Ozaydın, Ozkara & Cakir, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Educators concluded that the distance education offered a medium of communicating with their students (Anastasiades, 2020• Manesis et al, 2022. However, it cannot replace the team's dynamics within a school classroom, since it is a lonely method of learning (Ozaydın, Ozkara & Cakir, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These students also require a greater effort by the teacher in order to attract and maintain their attention and interest. Since an engagement to pedagogical issues is missing, students end up to simply keep in touch with the school reality (Manesis et al, 2022). In some cases, the students even abandon the course giving different excuses (Niemi & Kousa, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Το Υπουργείο Παιδείας ζήτησε να αξιοποιηθούν οι πλατφόρμες (e-me, eclass) για την παροχή εκπαίδευσης, χωρίς όμως να έχει προετοιμάσει κατάλληλα και εγκαίρως τα σχολεία και τους/τις εκπαιδευτικούς. Οι εκπαιδευτικοί για διάφορους λόγους (προβλήματα υποδομών, πεποιθήσεις, άγνοια, έλλειψη επιμόρφωσης), αν και αμφισβήτησαν έντονα την παροχή εξ αποστάσεως εκπαίδευσης, επειδή αντιλήφθηκαν ως εξέχουσα την ανάγκη να προσφέρουν στήριξη στους/στις μαθητές/μαθήτριες, προσαρμόστηκαν, και χωρίς να λάβουν υπόψη τον χρόνο, τον κόπο, τα προσωπικά έξοδα, αφού η διαδικασία πραγματοποιήθηκε κυρίως με ίδια μέσα, χρησιμοποίησαν κάθε πρόσφορο μέσο που είχαν στη διάθεσή τους (αποστολή ασκήσεων με τα μέσα κοινωνικής δικτύωσης, φύλλα εργασίας που έπαιρναν οι γονείς από το σχολείο, απλή τηλεφωνική επικοινωνία με τις οικογένειες), για να επικοινωνήσουν με τους/τις μαθήτριες/μαθητές και όχι μόνο τις προτεινόμενες πλατφόρμες (Manesis et al, 2022).…”
Section: η εκπαιδευτική πολιτική και ο σχεδιασμόςunclassified